Therapeutic potential of naturally derived carbon dots in sepsis-associated acute kidney injury - Lei Wang; Zhong-Yao Li; Chong-Lei Zhong; Zi-Yang Teng; Bin Wang; Asma Rehman; Li-Wen Han; Ke-Wu Zeng; Ji-Guo Zhang; Zhi-Yuan Lu (Chinese Medicine)
Abstract Background Sepsis is a life-threatening infectious disease characterized by an uncontrolled inflammatory response and consequent multi-organ dysfunction. The kidneys, as primary excretory organs with high blood flow, are particularly susceptible to damage during sepsis. Nonetheless, the existing treatment options for sepsis-associated acute kidney injury (SA-AKI) are still restricted. Nanomedicine, especially carbon dots (CDs), has attracted considerable interest lately for outstanding biomedical characteristics. Methods To avoid the generation of toxic effects, the natural CDs derived from Ziziphi Spinosae Semen (Z-CDs) were synthesized employing a hydrothermal method. The free radical scavenging capabilities of Z-CDs were evaluated by utilizing ABTS assay, NBT method, and Fenton reaction. A lipopolysaccharide (LPS)-stimulated RAW 264.7 cell model was used to explore the therapeutic potential of Z-CDs on cellular oxidative stress and inflammation. The CuSO4-induced zebrafish inflammation model and LPS-exposed SA-AKI mouse model were employed to assess the therapeutic efficacy of Z-CDs in vivo. Results The synthesized Z-CDs exhibited distinctive unsaturated surface functional groups, which confer exceptional biocompatibility and the ability to scavenge free radicals. Moreover, Z-CDs were particularly effective in eliminating excess reactive oxygen species (ROS) in cells, thus protecting mitochondrial function from oxidative damage. Notably, Z-CDs have demonstrated significant therapeutic benefits in protecting kidney tissue in SA-AKI mouse model with minimizing side effects. In mechanism, Z-CDs effectively reduced ROS production, thereby alleviating inflammatory responses in macrophages through the suppression of the NF-κB pathway. Conclusions This study developed a multifunctional nanomedicine derived from traditional medicinal herb, providing a promising pathway for the advancement of innovative drug therapies to treat SA-AKI.